(untitled) (Research, Society and Development, 2022)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder. Early diagnosis is a tool to minimize losses, however, some individuals are diagnosed in adulthood and there is a shortage of works aimed at this age group. Objectives: Understand and analyze the reasons that lead to late diagnosis of ASD and what are the functional and psychosocial impacts caused to adult patients who receive this diagnosis. Methodology: This is an integrative review about the impacts of late diagnosis of ASD in adults. The PICO strategy was used to prepare the guiding question. Furthermore, the descriptors “Late Diagnosis” were crossed; “Autistic Spectrum Disorder” and “Psychosocial Impact” in the following databases: Virtual Health Library (VHL); Scientific Electronic Library Online (SCIELO) and PubMed. Results and Discussion: From the 12 selected studies, it is noted that, as it is associated with childhood, there are few studies on ASD directed at the adult population. Thus, many people spend much of their lives with the symptoms of the disorder, but without receiving the diagnosis. This triggers losses and makes it impossible for the individual to seek interventions to improve their quality of life. Conclusion: After this review, we emphasize the importance of early diagnosis of ASD and the creation of new studies on the subject, in order to improve the quality of life of the adult population with the disorder, as well as the relief of symptoms that, many times, sometimes worsen due to the lack of specific treatments.